MORPHOLOGY AND CHEMICAL COMPOSITION OF ONION (ALLIUM CEPA L.) AND EXTRACTION METHODS FOR ONION OIL - Usmonova, Munavvar Shodiyor qizi; Xolmurodov , Bobur Baxrom o‘g‘li; Jurayev, Mirkomil Chori o‘g‘li (Educational Research in Universal Sciences, 2023)
This article explores the morphology and chemical composition of onion (Allium cepa L.), a widely cultivated and consumed vegetable with varieties of red, yellow, and white. The article highlights the nutritional value of onions, including their water content, carbohydrates, proteins, vitamins, minerals, and volatile oil. It delves into the historical significance of onions and their cultural symbolism. Furthermore, the article examines the chemical composition of onion fruits and leaves, including sugars, proteins, vitamins, minerals, and sulfur-containing compounds. It discusses the various extraction methods used to obtain onion oil, such as steam distillation, supercritical carbon dioxide extraction, and the distillation method. The main components of onion oil, particularly sulfur compounds, are also identified and their significance in flavor and medicinal properties is discussed.